Media Strategies to Face Disaffects of Consuming Social Media on Family - Mohammad Reza Taghavipour; Abdollah Bicharanlou (Religion & Communication)
In the age of network society formation, the nature of communication has been changed dramatically. These changes, especially by the development of social media have affected the family negatively and positively. While the optimum use of social media opportunities is advised, their disaffections should not be neglected. Thus this paper is to identify strategies to face disaffections of consuming social media on the family. To achieve the goal of the paper, 2 steps were taken; First, of all ,25 members of selected families were interviewed. As a result, 116 solitary codes were identified which were categorized into 13 categories and 6 topics. These topics included “dividing”, “anguish”, “miscomparison”, “access to disproportionate information”, “waste of time” & “the probability of dating”. Second, to achieve expert consensus on the media strategies, some questions were extracted of interviewee`s comments, and through purposive sampling 14 experts in 4 categories were selected and interviewed in 2 phases of Delphi panels. The categories included “communication professors”, “media executives”, “family researchers and experts”, “social network activists”. As the result, 41 strategies were identified. The strategies were classified into 7 topics: “independence or replacing”, “securing”, “empowerment of audience”, “referring to the family”, “persuasion of the audience”, “Explanation”, “negation of consumerism”.